Proceedings of the 39th SIGCSE Technical Symposium on Computer Science Education 2008
DOI: 10.1145/1352135.1352226
|View full text |Cite
|
Sign up to set email alerts
|

Identifying important and difficult concepts in introductory computing courses using a delphi process

Abstract: A Delphi process is a structured multi-step process that uses a group of experts to achieve a consensus opinion. We present the results of three Delphi processes to identify topics that are important and difficult in each of three introductory computing subjects: discrete math, programming fundamentals, and logic design. The topic rankings can be used to guide both the coverage of student learning assessments (i.e., concept inventories) and can be used by instructors to identify what topics merit emphasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(53 citation statements)
references
References 5 publications
(1 reference statement)
0
53
0
Order By: Relevance
“…Goldman et al [7] have identified important and difficult concepts in an introductory computing course. As a result they have generated a list of programming fundamental (CS1) topics that the teachers had rated both by how difficult and how important they think the topics are.…”
Section: Drop Out Reasons and Difficulties Related To Learning Programentioning
confidence: 99%
“…Goldman et al [7] have identified important and difficult concepts in an introductory computing course. As a result they have generated a list of programming fundamental (CS1) topics that the teachers had rated both by how difficult and how important they think the topics are.…”
Section: Drop Out Reasons and Difficulties Related To Learning Programentioning
confidence: 99%
“…Our preliminary findings for Step 1 above were previously published [Goldman et al 2008], so in this article, we present additional and expanded information on our findings for each of the three computing subjects we are focusing on. Because we seek to develop CIs that are widely applicable, we sought the opinions of a diverse group of experts using a Delphi process (described in Section 3), an approach used to develop some previous CIs [Gray et al 2003;Streveler et al 2003].…”
Section: · 5:mentioning
confidence: 83%
“…In a study of experts, Goldman et al [7] found that experts ranked "tracing and designing recursive algorithms" to be among the most difficult of thirty-two fundamental programming concepts. Further, experts did not agree on whether "tracing and designing recursive algorithms" was an appropriate topic for a first course.…”
Section: Related Workmentioning
confidence: 99%